Sustainability and action research in universities: Towards knowledge for organisational transformation. Issue 4 (6th July 2015) - Wooltorton, Sandra; Wilkinson, Anne; Horwitz, Pierre; Bahn, Sue; Redmond, Janice; Dooley, Julian
Abstract : Purpose: – Academic approaches to the challenge of enhancing sustainability in research in university contexts illustrate that universities are affected by the very same values and socio-ecological issues they set out to address, making transformation difficult at every level. A theoretical and practical framework designed to facilitate cultural transformation is therefore necessary for conceptualising the problem and delineating possible strategies to enhance sustainability in research. Organisational change is also required, possibly on a university-by-university basis, where cross-institutional learning may be possible with personal behaviours that enhance collaboration across disciplinary and administrative divides. Design/methodology/approach: – This paper contends that action research, in particular, community action research (CAR), offers the best approach to this task because it focusses on learning and change, and these are both essential to cultural transformation. A case study from a university in Western Australia is used to demonstrate this approach. Findings: – The case study analysis shows some evidence for the presence of knowledge for organisational transformation, and that future monitoring cycles will be needed to detect the extent of the change. Originality/value: – The paper introduces CAR as an approach to advance the change for sustainability in higher education and discusses some of the implications for universities who are looking to incorporate sustainability as a major part of their culture.